Molecular Glues and Molecular Glue Degraders: Mechanisms, Design, and Therapeutic Applications - Shi, Haonan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Molecular glues and molecular glue degraders appear to be a fast-growing class of therapeutic agents that selectively modulate protein-protein potential interactions and can enhance the selective degradation of proteins. These small molecules are providing the possibility to target proteins that previously thought to be very challenging or inaccessible that are involved in a host of diseases. The present review focuses on describing the basic concepts of molecular glues and the rationale behind the interactions and the general concept that drives their design. Special attention is paid to their uses in cancer therapy, neurodegenerative diseases, and infections therapy. Exploring new therapeutic targets and drugs based on the molecular glue degraders’ ability to recognize and bind E3 ubiquitin ligases and promote ubiquitination proteolysis of specific proteins. Furthermore, the review looks at some of the limitations and the difficulties in the creation of these agents, as well as that potential in the field of pharmacogenomics. Thus, future expansion of molecular glue with state-of-the-art technologies including artificial intelligence and CRISPR is expected to extend its therapeutic applicability; evidently a step-up for targeted therapies. In this review, it offers the state-of-art on molecular glue studies and future direction for such work.